2018
DOI: 10.1016/j.jeconbus.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Do fintech lenders penetrate areas that are underserved by traditional banks?

Abstract: Fintech has been playing an increasing role in shaping financial and banking landscapes. In this paper, we use account-level data from LendingClub and Y-14M data reported by U.S. banks with assets over $50 billion to examine whether the fintech lending platform could expand credit access to consumers. We find that LendingClub's consumer lending activities have penetrated areas that may be underserved by traditional banks, such as in highly concentrated markets and in areas that have fewer bank branches per cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 293 publications
(144 citation statements)
references
References 31 publications
8
129
0
7
Order By: Relevance
“…Our previous research in Jagtiani and Lemieux (2018) presented evidence that fintech lenders fill credit gaps in areas where bank offices may be less available and provide credit to creditworthy borrowers that banks may not be serving. Our further research in this paper finds that loans from fintech lenders seem to be "appropriately" risk priced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research in Jagtiani and Lemieux (2018) presented evidence that fintech lenders fill credit gaps in areas where bank offices may be less available and provide credit to creditworthy borrowers that banks may not be serving. Our further research in this paper finds that loans from fintech lenders seem to be "appropriately" risk priced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some fintech lenders can identify whether the loan applications are submitted from a high-crime area or in an area where factories are being shut down or relocated. Previous studies have found evidence that local economic information could serve as a possible relevant source of nontraditional information by fintech lenders (Alyakoob, Rahman, & Wei, 2017;Bertsch, Hull, & Zhang, 2016;Buchak, Matvos, Piskorski, & Seru, 2017;Chen, Hanson, & Stein, 2017;Crowe & Ramcharan, 2013;Havrylchyk, Mariotto, Rahim, & Verdier, 2018;Jagtiani & Lemieux, 2018).…”
Section: The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Access to funds pertains to the ability of individuals or businesses to obtain financial services within reach. Several factors are documented to affect access to funds in developing countries, but the unwillingness of traditional banks to invest in areas deemed unprofitable remains a key challenge [4]. Per statistics, financial access remains a key challenge in most developing economies due to the nature of settlement and economic conditions, which places majority in rural areas undesired by traditional banks.…”
Section: Financial Accessibilitymentioning
confidence: 99%
“…Further, statistics indicate that sub-Sahara Africa alone holds over 50% share of the total global customer base, and with the mobile phone penetration expected to grow up to 500 million subscribers by the year 2020, the region has huge potential in this domain of FinTech (the Mobile Economy Sub-Saharan Africa 2018 report). The introduction of mobile payment in sub-Sahara Africa championed mainly by Telecos has been hailed as one of the grand financial innovations to improve the status of financial inclusion in the region as a result of the failed efforts of traditional banks to financially include many in preceding decades [3,4].…”
Section: Introductionmentioning
confidence: 99%